Validation of a commercial human ELISA to measure hyaluronic acid concentration in feline plasma. (January 2022) - Shaw, Kaela E.; Bersenas, Alexa M.; Bateman, Shane W.; Blois, Shauna L.; Wood, R. Darren
Our goal was to validate a human hyaluronic acid (HA) ELISA (Hyaluronic acid plus ELISA; TECOmedical Group) for use in feline plasma. Plasma from 5 healthy cats and 5 critically ill cats was used for validation of the assay. Validation methods performed included intra- and inter-assay variability, spike-and-recovery, and dilutional linearity. All measurements were performed in duplicate. The precision study revealed good intra-assay CV of 7.4–8.9%; inter-assay CV was 3.4–4.2%. Extraction efficiency via spiking tests yielded mean recovery of 89.6%. The assay met criteria for acceptable linearity using 3 serial dilutions. Our results demonstrate that this commercial HA ELISA had acceptable analytical performance using feline plasma and could be a useful tool in the veterinary clinical research setting.